Using the simulation program of the DA-42T aircraft central data system operation in the educational process of the university - A. S. Knyazev; A. S. Antonenko; M. A. Loptev; E. M. Zhdanov (Научный вестник МГТУ ГА)
During training sessions in an aviation university, it is advisable to demonstrate samples of aeronautical equipment, individual elements of systems and units or to use some specialized stands and posters. However, when conducting classes online, not all these materials can be used, since it is not always accomplishable to demonstrate them in dynamics and thereby to ensure the students’ complete understanding of the object being studied. The article deals with the issue of enhancing visibility and efficiency of training pilot trainees by using software applications during the educational process, which simulate the operation of the Central Data System, information from which is displayed in the real aircraft in the form of frames on multipurpose displays in the cockpit. Working with the developed program allows student pilots to gain the required practical skills while interacting with the avionics suite. In order to implement the simulation program of the Central Data System operation into the educational process, I-frames, shown on the DA-42T aircraft multipurpose displays, were reproduced. The content of the developed frames completely repeats the DA-42T aircraft indication, which contributes to improving the quality of training and honing practical skills for aircraft operation. The structure and the procedure of designing the program to simulate the Central Data System operation are described. The selection of software for the development of the Central Data System simulation program is substantiated. The feasibility of integrating the developed program into the flight simulator is described. The applicability of using the software program for distance training of aviation specialists, as well as of the implementation of the results obtained into the educational process of aviation universities is provided.